Effect of administering a diet contamined with fumonisins on the kidneys of wistar rats (Acta Scientiarum. Biological Sciences, 2014)
Fumonisins (FBs) are mycotoxins produced by Fusarium molds. Several works have shown contamination of maize by this toxin. Fumonisin B1 (FB-1) is found in greatest proportion (about 70%), resistant to several industrialization processes. In that context, the objective of this work was to analyze the effect of administering a diet contaminated with FB-1 on the morphophysiology of the kidneys of 21-day old male Wistar rats. The animals were divided into 2 groups: G0 (with animals receiving feed free of FBs) and G6 (6mg of FB1 kg-1 of feed). The diet was administered during 42 days. After that period, the animals were placed in metabolic cages for urine collection, blood was collected for analysis of plasma creatinine, and the kidneys were fixed and stained with Masson's trichrome. We observed that FB1 administration did not affect feed intake, body weight gain and animal growth. The normal levels of plasma creatinine suggest that the toxin did not lead to glomerular lesion. There was also no change in water intake, osmolarity and excretion of sodium in urine. However, there was a significant increase in urine volume and potassium excretion in urine, with mild tubulointerstitial changes in the outer cortex for the group receiving the mycotoxin.